Transient measurement of phononic states with covariance-based stochastic spectroscopy - Sparapassi, Giorgia; Cavaletto, Stefano M.; Tollerud, Jonathan; Montanaro, Angela; Glerean, Filippo; Marciniak, Alexandre; Giusti, Fancesca; Mukamel, Shaul; Fausti, Daniele (Light: Science & Applications, 2022)
We present a novel approach to transient Raman spectroscopy, which combines stochastic probe pulses and a covariance-based detection to measure stimulated Raman signals in alpha-quartz. A coherent broadband pump is used to simultaneously impulsively excite a range of different phonon modes, and the phase, amplitude, and energy of each mode are independently recovered as a function of the pump–probe delay by a noisy-probe and covariance-based analysis. Our experimental results and the associated theoretical description demonstrate the feasibility of 2D-Raman experiments based on the stochastic-probe schemes, with new capabilities not available in equivalent mean-value-based 2D-Raman techniques. This work unlocks the gate for nonlinear spectroscopies to capitalize on the information hidden within the noise and overlooked by a mean-value analysis.
CRIS-Team Scopus Importer:2022-07-20